The Influence of Technology Use, Perceived Ease of Use and Facilitating Conditions on Stock Investment Decisions in the Sharia Online Trading System (SOTS) (Case Study of UINSU Medan Students) - Manik, Alfia Rahman; Soemitra, Andri; Harahap, Muhammad Ikhsan (Journal of Applied Accounting and Taxation, 2026)
The growing public interest in Sharia-compliant investments has driven the need to utilize technology that facilitates access to the capital market. One emerging innovation is the Sharia Online Trading System (SOTS), a digital-based Sharia-compliant stock trading platform designed to help Muslim investors transact in accordance with Sharia principles. However, its use still garners less than favorable public perception, primarily because the system is still integrated with conventional mechanisms. This study aimed to determine the influence of Technology Use, Perceived Ease of Use, and Facilitating Conditions on stock investment decisions through SOTS. The method used was a quantitative approach with a causal associative approach. The study sample consisted of 85 active SOTS student users selected through purposive sampling based on specific criteria. Data were collected online using a Likert-scale questionnaire. The results of multiple linear regression analysis showed that the three independent variables simultaneously had a significant influence on stock investment decisions, with a coefficient of determination (R²) of 0.745. Partially, Technology Use was the most dominant variable compared to the other variables. These findings confirm that the success of investing through Sharia-compliant digital platforms depends not only on the quality of the technology used, but also on the perceived ease of use of the system and the available infrastructure support. Therefore, system development and education for potential investors are crucial steps to increase public participation in Sharia-compliant stock investing in the digital era.